Corrosion-erosion behavior of MgAl2O4 spinel refractory in contact with high MnO slag. Issue 17 (1st December 2017) - Jeon, Junmo; Kang, Youngjo; Park, Joo Hyun; Chung, Yongsug
Abstract: The corrosion and erosion behavior of spinel refractory of different compressive strength has been investigated for refractories in contact with a high MnO slag for producing manganese ferroalloys. The finger rotating test (FRT) was adopted to evaluate the degradation behavior at 1550 °C under a rotating condition of 150 rpm. The sample with higher compressive strength (Sample C1) showed higher corrosion resistance than Sample C2. In Sample C1, the refractory progressively corroded from the surface to the inner region by chemical corrosion, while mechanical erosion of the refractory suddenly occurred in Sample C2 as a result of the penetration of the slag within the refractory and the rotating energy.